Synergy of National Identity and Universal Norms - Arena Barakallah (Indonesian Journal of Pancasila and Global Constitutionalism, 2025)
Pancasila, as the foundational ideology of Indonesia, plays a strategic role in maintaining national identity amid the pressures of global constitutionalism, which emphasizes universal values such as human rights, democracy, and the supremacy of law. This study analyzes how Pancasila can synergize with global norms without compromising national sovereignty and collective values. Employing a normative juridical and comparative approach, the research examines key constitutional documents like the 1945 Constitution and the formulation of Pancasila, alongside relevant International legal instruments, supported by a review of national and international literature and policies. The findings demonstrate that Pancasila offers an inclusive and flexible legal paradigm capable of accommodating democratic and human rights values within Indonesia’s unique cultural and social framework. Through principles of deliberation, social justice, and national unity, Pancasila balances national interests and international obligations, distinct from the individualistic models prevalent in Western legal systems. The challenges posed by globalization underscore the need to strengthen Pancasila-based legal policies and education to safeguard sovereignty while enabling Indonesia’s active participation in the global legal order. Thus, Pancasila is not merely an ideological foundation but an adaptive instrument that enhances Indonesia’s position in navigating global complexities. This study contributes a balanced and constructive perspective to Indonesian constitutional literature, emphasizing the harmonization of nationalism and universalism in the global era. This analysis highlights that Pancasila not only anchors Indonesia’s national identity but also provides a resilient and adaptive legal framework capable of engaging with global constitutionalism.